“Adequate Financing for Small, Medium & Micro Enterprises Through Financial Inclusions: An Accessible Framework of Rural Markets” - Dr Pooja Neemey Dr Nidhi Singhal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
History bears the testimony to the relationship between development of financial markets and economic growth, thus leading to the reduction of poverty on a larger scale. It has become more so crucial for economies like India because the lack of it inevitably prevents people from gaining access to available resources and thus pushes them to an inescapable cycle of poverty. Access to adequate financing for small, medium and even micro sized enterprises is essential for an economy considering the reach and numbers such markets offer. Financial inclusion comes as an omen, a sign for better future and seamless social inclusion because a population that identifies itself best with the rest of the society contributes more positively towards economic progress. Many banks, such as Union Bank of India, Yes Bank etc. have started several programs specially targeted towards rural people in India. But unfortunately, financial systems in India till date have not seen enough in uplifting the lives of the bottom of the pyramid masses because providing basic financial services such as bank accounts, credit, and insurance have a higher cost for that people. The paper briefly outlines the requirement and role of financial inclusion